Understanding the “Balancing Act” of Turkey in the Russia-Ukraine War - ERTÜRK, AHMET CEMAL (IGI Global, 2023)
Since the beginning of the conflict, Turkey, as a regional powerhouse, has remained intact in its position as the “honest broker.” In a nutshell, Turkey has been trying to consolidate a balance between the resurgence of Russian aggressiveness and the Western aspirations to protect Ukraine at all costs. For so many in the West, Turkish actions were defined as even damaging at some point to the causes of NATO and the EU. Nevertheless, Turkey's role conception in this war is nothing new and rooted very well back to the earlier Republican experience with the Black Sea. In other words, Turkish foreign policy towards the Black Sea and Ukraine/Russia has always leaned toward a strategic behavior of balancing these significant powers. The latest act has been no different from a Turkish way of “sticking with the plan.” Therefore, deciphering the dynamics of this role is undoubtedly a must to undercover the geopolitical interest of Turkey from the region amid a fully-fledged war. This chapter proposes three related sections to understand and analyze the story's Turkish side.
The Russia-Ukraine War and Its Consequences on the Geopolitics of the World
▪️ Source Title: The Russia-Ukraine War and Its Consequences on the Geopolitics of the World.